The relationship among plasma copeptin, carboxyhemoglobin, and lactate levels in carbon monoxide poisoning. (March 2020) - Ozkan, S; Salt, O; Durukan, P; Sen, A; Bulbul, E; Duman, A; Kavalci, C
Objective: The aim of our study is to determine whether there is a change in the plasma levels of copeptin and there is a relationship among the plasma levels of carboxyhemoglobin (COHb), lactate, and copeptin levels in patients presenting to the emergency department with carbon monoxide (CO) poisoning. Methods: Fifty-seven patients admitted to the emergency department with CO poisoning were included in the study. The blood samples of the patients were collected on arrival 0th, 6th, and 12th hours for copeptin, lactate, and COHb levels. Data were analyzed using SPSS-17 statistical software. Results: Arrival serum copeptin levels of the patients were compared to copeptin levels of healthy individuals and a statistically significant difference was found between them ( p = 0.008). There was a statistically significant difference between the arrival levels of copeptin and 6th-hour ( p = 0.006) and 12th-hour ( p = 0.001) levels of copeptin. There was no significant difference between 6th-hour and 12th-hour copeptin levels ( p = 0.51). In terms of serum lactate levels, there was a significant difference between arrival and 6th h ( p < 0.001), arrival and 12th h ( p < 0.001), and 6th and 12th h ( p < 0.001). Likewise, in terms of serum COHb levels, there was a significant difference between arrival and 6th h ( p < 0.001), arrival and 12th h ( p < 0.001), and 6th and 12th h ( p < 0.001). There was a positive correlation between COHb and lactate levels on arrival ( r = 0.52; p = 0.001). Conclusion: Copeptin as a stress hormone can be used in the diagnosis and monitoring of patients with CO poisoning. However, the copeptin level was not superior to COHb and lactate levels.